Aplicación de un sistema de contabilidad comercial y análisis financiero, en "ÓPTICAS GOLD” en la ciudad de Zamora Chinchipe, durante el periodo de noviembre y diciembre del 2015 - Godoy Godoy, Russbel Iván (2016)
This thesis entitled "APPLICATION OF A SYSTEM OF BUSINESS ACCOUNTING AND FINANCIAL ANALYSIS IN" OPTICAL GOLD "IN THE CITY OF ZAMORA CHINCHIPE, DURING NOVEMBER AND DECEMBER 2015" is aimed at applying accounting tools to enhance your efficient development and development of the company under study, the main focus was oriented to propose an accounting system that allows to know the economic and financial situation, which will serve for decision-making and achievement of goals and business objectives. In the development of this work we identify the needs of the company, having raised main objective is the application of an accounting process for decision-making; first theoretical foundations that sustain for the development and support of it, in practice we apply the system of multiple account are presented; starting from the initial inventory that served to determine the stocks of all assets owned by the company, then we developed the Plan and Accounting Manual which facilitated the identification and proper use of accounts, perform main and auxiliary records to centralize and quantify the economic movement and finally present the financial statements that show clearly and realistically the economic results obtained in the period. Una vez aplicado el proceso contable, concluimos que la aplicación práctica permitió obtener resultados reales a través de los Estados Financieros, por lo que se recomienda aplicar la contabilidad como herramienta que coadyuva a tener un mejor control de las operaciones que se efectúan dentro de la empresa; registrar el Libro Diario diseñado con la finalidad de determinar los ingresos y salidas de dinero; realizar la actualización constante del Inventario ya que este permitirá establecer claramente los bienes, derechos y obligaciones que posee la entidad con el fin de incrementar la rentabilidad empresarial que se obtiene al finalizar un ciclo económico, en el mediano o largo plazo.